Osteochondroma of the distal tibia in an 8‐year‐old child: Do we need to excise a benign tumor?. Issue 12 (9th September 2020) - Galanis, Nikiforos; Delniotis, Ioannis; Noussios, George; Katsourakis, Anastasios; Kitridis, Dimitrios; Leidinger, Benedikt; Givissis, Panagiotis
Abstract: Osteochondromas are benign tumors that can be responsible for angular deformities, limb‐length discrepancy, and impending fractures of the neighboring bones. The risk of future fractures and joint malalignment is an indication for surgical intervention. Abstract : Osteochondromas are benign tumors that can be responsible for angular deformities, limb‐length discrepancy, and impending fractures of the neighboring bones. The risk of future fractures and joint malalignment is an indication for surgical intervention.